The Dreams of Pecola Breedlove and Richard Wright - Lucie Dlouhá (American and British Studies Annual, 2008)
The paper introduces two child protagonists, Pecola Breedlove and Richard Wright, and analyzes and compares their difficult childhoods, influenced by the tragic impact of racisms and long-time effects of slavery.